Oropouche fever diagnosed in Milan, Italy in returning travellers from Rio de Janeiro, March 2024, and Cuba, July 2024 - Mancon, Alessandro; Gagliardi, Gloria; Giacomelli, Andrea; Vezzosi, Luigi; Gori, Andrea; Antinori, Spinello; Cereda, Danilo; Gismondo, Maria Rita; Mileto, Davide (Journal of travel medicine, 2024)
We describe two cases of Oropouche fever in travellers from Brazil, late March 2024, and from Cuba, July 2024. The Oropouche virus was carried outside the Americas before the Cuba outbreak, requiring screening in febrile travellers from Latin America. Studies on possible vectors and reservoirs in new areas should be implemented.